2020
DOI: 10.1111/jipb.13002
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of circular RNA N6‐methyladenosine in moso bamboo (Phyllostachys edulis) using nanopore‐based direct RNA sequencing

Abstract: N6‐methyladenosine (m6A) is a prevalent modification in messenger RNAs and circular RNAs that play important roles in regulating various aspects of RNA metabolism. However, the occurrence of the m6A modification in plant circular RNAs has not been reported. A widely used method to identify m6A modifications relies on m6A‐specific antibodies followed by next‐generation sequencing of precipitated RNAs (MeRIP‐Seq). However, one limitation of MeRIP‐Seq is that it does not provide the precise location of m6A at sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 91 publications
0
32
0
Order By: Relevance
“…The products were then eluted in 21-μl Elution Buffer (1-μl elution was used to quantify the concentration using QubitTM dsDNA HS Assay Kit), mixed with nuclease-free water and RNA Running Buffer (RRB) to a total of 75-μl library prior to loading onto the flow cell, and ran on GridION (repeat1) and MinION (repeat2) sequencer, respectively. The RNA strand was ligated to the 1D sequencing linker bearing the RNA motor protein, which ensured efficient translocation of RNA rather than cDNA through the Nanopore [27,28]. Two independent biological repeats were sequenced using a GridION X5 sequencer with flow cell R9.4.1 and a MinION flow cell (FLO-MIN106) to generate real-time single-molecule sequencing.…”
Section: Construction Of Library and Direct Rna Sequencingmentioning
confidence: 99%
“…The products were then eluted in 21-μl Elution Buffer (1-μl elution was used to quantify the concentration using QubitTM dsDNA HS Assay Kit), mixed with nuclease-free water and RNA Running Buffer (RRB) to a total of 75-μl library prior to loading onto the flow cell, and ran on GridION (repeat1) and MinION (repeat2) sequencer, respectively. The RNA strand was ligated to the 1D sequencing linker bearing the RNA motor protein, which ensured efficient translocation of RNA rather than cDNA through the Nanopore [27,28]. Two independent biological repeats were sequenced using a GridION X5 sequencer with flow cell R9.4.1 and a MinION flow cell (FLO-MIN106) to generate real-time single-molecule sequencing.…”
Section: Construction Of Library and Direct Rna Sequencingmentioning
confidence: 99%
“…Through depletion of rRNA, treatment with RNase R to digest linear RNAs and m6A-modified RNA immunoprecipitation sequencing (MeRIP-seq), m6A modification of circRNAs has been found to exist widely. In plant, Wang et al (2020) found that about 10% of the EcRNAs contained m6A sites in moso bamboo. In human embryonic stem cells (hESCs) and HeLa cells, Zhou et al (2017) identified 1,404 m6A circRNAs and 987 m6A circRNAs, respectively, and they found that m6A circRNAs were expressed in cell-type-specific methylation patterns.…”
Section: M6a Modification Of Circrna Widely Existed M6a Modification Of Circrnasmentioning
confidence: 99%
“…With the progress of high-throughput sequencing and antibody-specific enrichment technology, a new detection method, methylated RNA immunoprecipitation sequencing (MeRIP-seq), was developed with the advantage of identifying almost all m 6 A modifications in different types of RNA, such as mRNA (77), lncRNA (78) and circular RNA (79). In MeRIP-seq, specific antibody of m 6 A is used to extract co-immunoprecipitated RNA fragments, which are further identified using high-throughput sequencing (80).…”
Section: Merip-seqmentioning
confidence: 99%